2014
DOI: 10.1097/psy.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Socioeconomic Disadvantage and Prediabetes and Diabetes in Later Life

Abstract: Objective We examined the relationship between childhood socioeconomic status (SES) and glucoregulation in later life and used a life-course framework to examine critical periods and underlying pathways. Methods Data came from the MIDUS (Midlife in the U.S.) national study (n=895). Childhood SES indicators retrospectively reported at MIDUS I were used to create a childhood SES disadvantage index. Adult SES disadvantage and potential pathways were measured at MIDUS I and included waist circumference, depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 36 publications
3
36
2
Order By: Relevance
“…59 Such stress may lead to metabolic disorders such as insulin resistance and diabetes. 60,61 Furthermore, it is well documented that HIV-infected women experience a high number of stressors. Among HIV-infected women in the WIHS, 31% reported childhood sexual abuse, 66% reported domestic violence within their lifetime, and 21% reported domestic violence within the past 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…59 Such stress may lead to metabolic disorders such as insulin resistance and diabetes. 60,61 Furthermore, it is well documented that HIV-infected women experience a high number of stressors. Among HIV-infected women in the WIHS, 31% reported childhood sexual abuse, 66% reported domestic violence within their lifetime, and 21% reported domestic violence within the past 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the importance of early life socioeconomic conditions for T2DM [13], whether it was only via adulthood socioeconomic conditions [3, 6, 8, 10, 14] or also independently [7, 9, 11, 12, 15]. Some of these studies confirm the pathway via (abdominal) obesity [3, 9, 12, 14, 15]. In other studies, the relationship between early life socioeconomic conditions and T2DM was particularly found in women [3, 7, 9, 11].…”
Section: Discussionmentioning
confidence: 92%
“…The progression towards T2DM can more easily be prevented and the prediabetic state can even be inverted [23, 2628]. Only one previous study examined the association of early life socioeconomic conditions with prediabetes; the authors reported that they only found evidence for an indirect association [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Following prior MIDUS research (Gruenewald et al, 2012; Karlamangla et al, 2013; Tsenkova et al, 2014), a childhood socioeconomic disadvantage score was constructed by summing across three retrospectively-reported indicators of SES in participants‘ childhood and adolescence: family finances (worse off than others=2; same as average family=1; better off than others=0), highest parental education (less than high school=2; high school=1; college or more=0), and welfare for ≥6 months (ever=2; never=0).…”
Section: Methodsmentioning
confidence: 99%